The welfare impacts of market channel choice by smallholder farmers in Tanzania. Issue 7 (3rd October 2017) - Mmbando, Frank E.; Wale, Edilegnaw Z.; Baiyegunhi, Lloyd J.S.
ABSTRACT: This article analyses the impact of market channel choice on household welfare by maize and pigeon pea smallholder farmers in Tanzania, using a multinomial endogenous treatment approach. The study utilises farm household-level data collected from a randomly selected sample of 700 smallholder farmers. The results show that participation with traders in nearby markets and wholesalers in nearby towns have a positive effect on consumption expenditure per capita relative to brokers at the farmgate, for both maize and pigeon pea-farming households. The study suggests that interventions that aimed at inclusion of smallholder farmers in more profitable markets could improve household welfare and reduce poverty among rural households.